GFI1B mutation causes a bleeding disorder with abnormal platelet function. (November 2013) - Stevenson, W. S.; Morel‐Kopp, M.‐C.; Chen, Q.; Liang, H. P.; Bromhead, C. J.; Wright, S.; Turakulov, R.; Ng, A. P.; Roberts, A. W.; Bahlo, M.; Ward, C. M.
Summary Background GFI1B is a transcription factor important for erythropoiesis and megakaryocyte development but previously unknown to be associated with human disease. Methods A family with a novel bleeding disorder was identified and characterized. Genetic linkage analysis and massively parallel sequencing were used to localize the mutation causing the disease phenotype on chromosome 9. Functional studies were then performed in megakaryocytic cell lines to determine the biological effects of the mutant transcript. Results We have identified a family with an autosomal dominant bleeding disorder associated with macrothrombocytopenia, red cell anisopoikilocytosis, and platelet dysfunction. The severity of bleeding is variable with some affected individuals experiencing spontaneous bleeding while other family members exhibit only abnormal bleeding with surgery. A single nucleotide insertion was identified in GFI1B that predicts a frameshift mutation in the fifth zinc finger DNA‐binding domain. This mutation alters the transcriptional activity of the protein, resulting in a reduction in platelet α‐granule content and aberrant expression of key platelet proteins. Conclusions GFI1B mutation represents a novel human bleeding disorder, and the described phenotype identifies GFI1B as a critical regulator of platelet shape, number, and function.